2021
DOI: 10.3390/cryst11020153
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Activation Process of Carbon Black Based on Structural Parameters Obtained by XRD Analysis

Abstract: In the present study, carbon black activated by CO2 gas was examined through XRD analysis, especially with regard to changes in its structural parameters. Based on the results, its activation process was thoroughly analyzed. The activation process was controlled by isothermally activating the carbon black inside a reaction tube through which CO2 gas flowed. With this approach, the degree of activation was varied as desired. At an early stage of the activation process, the amorphous fraction on the carbon black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(50 citation statements)
references
References 44 publications
(51 reference statements)
4
46
0
Order By: Relevance
“…It should be noted that the peak corresponding to the graphite structure has a diffuse left shoulder. This peak shape is associated with the presence of LGC [ 40 ] or turbostratic graphite, [ 41 ] in which the interplanar distance d002 is larger than for highly graphitizable carbon (HGC). It was found in ref [40].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the peak corresponding to the graphite structure has a diffuse left shoulder. This peak shape is associated with the presence of LGC [ 40 ] or turbostratic graphite, [ 41 ] in which the interplanar distance d002 is larger than for highly graphitizable carbon (HGC). It was found in ref [40].…”
Section: Resultsmentioning
confidence: 99%
“…The number of active sites is strongly dependent upon porosity or surface area as they are associated with edges or defects on the surface [30,31]. The higher reactivity of chars obtained during pyrolysis in CO 2 atmosphere can by caused by the inclusion of oxygen and elevated total surface area, leading to the formation of new pores or the closing of pores opened by CO 2 [32,33]. Hence, the atmosphere in which the pyrolysis of tire waste was carried out affected the above-mentioned properties and, consequently, the reactivity of the received tire char.…”
Section: Analysis Of Tga Resultsmentioning
confidence: 99%
“…Hence, the atmosphere in which the pyrolysis of tire waste was carried out affected the above-mentioned properties and, consequently, the reactivity of the received tire char. It can be concluded that, at the stage of pyrolysis in an atmosphere of carbon dioxide, there is an initial activation of the char consisting of the development of a porous structure [33], which translates into its greater reactivity. In the work [15], it was found that the differences of pore volumes of chars obtained under N 2 and CO 2 flows were most likely caused by a difference in the diffusivity of volatiles in the two different atmospheres.…”
Section: Analysis Of Tga Resultsmentioning
confidence: 99%
“…Based on EDS signal and mapping results, the peaks at 9.59°, 15.12°, 19.20°, 28.97°, and 49.24° could be related to a phase or various phases of carbon (graphite, graphite oxide, graphite with Ru intercalated, or a mixture of these phases) [ 14 , 19 , 20 , 21 , 22 , 23 , 24 ]. Nevertheless, without further information, it is not possible to confirm that.…”
Section: Resultsmentioning
confidence: 99%